Credit risk management - Drlíčková, Marie (2019)
This bachelor thesis deals with credit risk of commercial banks. The aim of the thesis is to describe methods used to manage credit risk of the largest Czech banks and to examine the current situation in the Czech banking sector: to evaluate the level of regulatory capital, to describe risk exposures and structures of loans in the system as a whole and separately in the three selected banks. The data is drawn from statistics published by the Czech National Bank, financial results and annual reports of the individual banks. In the theoretical part, credit risk, credit risk management methods and Basel concepts are characterised. The empirical part focuses on the comparison of selected methods in the Czech banks.